Employment Impacts of the COVID-19 Pandemic across Metropolitan Status and Size - Seung Jin Cho; Jun Yeong Lee; John V. Winters (Institute of Labor Economics (IZA), 2020)
We examine effects of the COVID-19 pandemic on employment losses across metropolitan area status and population size. Non-metropolitan and metropolitan areas of all sizes experienced significant employment losses, but the impacts are much larger in large metropolitan areas. Employment losses manifest as increased unemployment, labor force withdrawal, and temporary absence from work. We examine the role of individual and local area characteristics in explaining differing employment losses across metropolitan status and size. The local COVID-19 infection rate is a major driver of differences across MSA size. Industry mix and employment density also matter. The pandemic significantly altered urban economic activity.
Keywords: J2; R2; 330; COVID-19; pandemic; employment; agglomeration; urbanization; cities; density